FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (Studi Empiris pada seluruh Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2012) - Fakhri -; Vince Ratnawati; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research is to explore the influence of the leverage, profitability, board size, the size of the company, the status of the company which is categorized as a company 'owned by the State, and institutional ownership affect to corporate social responsibility.The population in this research are listed companies (listing) in Indonesia Stock Exchange (IDX) 2012. The sampling design of this research is purposive sampling. Used in this research as technical analyse for test hypothesis multiple regression on the model proposed researchers using SPSS software version 19.0.The results of this research showed that board size, the size of the company, and the status of the company significant influence to corporate social responsibility. While the leverage, profitability, and institutional ownership unable to influence corporate social responsibility.Keywords: DER, ROA, BOC, the size of the company, the status of the company, institutional ownership, and CSR